Perioperative Safety and E?cacy of Pre-Surgical Multimodal Analgesia versus Intravenous Opioids in Children Undergoing Infraumbilical Urogenital Surgery - S Jani Noopur; P Butala Bina (Academia Anesthesiologica International, 2021)
Background: MMA (multimodal analgesia) alleviates pain through blockade of multiple nociceptive and inflammatory pain receptors along the pain pathway. Thus it maximizes pain control and minimizes drug induced adverse effects especially of opioids. We studied safety and efficacy of MMA comprising anti-inflammatory, local anaesthetics and alpha 2 agonist (in caudal block) against conventional opioid analgesia in children undergoing infra-umbilical urogenital surgery. Subjects and Methods: A randomized, prospective, single blind study was conducted in 40 patients aged between 1-8 years. After pre-medication, patients were given general anaesthesia with controlled ventilation via LMA. In Multimodal analgesia group, pre-surgical caudal block was given with Inj.Bupivacaine 0.25 %( 1ml/kg) +Inj.Clonidine (1mcg/kg).Paracetamol 30mg/kg inserted per rectally. In Opioid group, pre-surgical intravenous Fentanyl (2 mcg/kg) was given. Intra-operative fentanyl requirement, hemodynamic parameters ,sevoflurane dial concentration, side effects like nausea , vomiting, respiratory depression, emergence agitation, excessive sedation and post-operative fentanyl requirement(0.5mcg/kg, on demand/FLACC score>4 at 1,4,6 hrs) were noted. Patients were observed for 6 hrs in postoperative period. Result: We found significant increase in postoperative analgesic requirement in opioid group (18/20; p<0.001), while intra-operative opioid requirement was stastically insignificant between both the groups (p=0.17).Though linear decreasing trend in intraoperative inhalational agent requirement was observed in MMA group. Both the groups were comparable in terms of adverse effects. Conclusion: Presurgical MMA with caudal block and rectal paracetamol is safe and efficacious in children undergoing infraumbilical surgery.